PENINGKATAN HASIL BELAJAR PASSING BAWAH MELALUI MODIFIKASI PERMAINAN KOMPAS BOLVI PADA SISWA KELAS V SD NEGERI 01 DUWET KEC BOJONG KAB PEKALONGAN TAHUN 2013/2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
This study is action research with subjects of this study were fifth grade students of SD Negeri 01 Duwet which consists of 25 students . The variables of this study are student learning outcomes in learning volleyball on material passing down . Data collection techniques in this study consist of a class action practice test method , observation , and documentation . The analysis technique used is descriptive analysis using the techniques of classical completeness percentages are compared with indicators of success . The results showed an increase in the average acquisition value and the percentage of student mastery . In the first cycle, the average value is 60.97 students increased to 71.50 in the second cycle . While the percentage of completeness in the first cycle was 44 % with a qualifying was increased to 76 % with higher qualifications in the second cycle . Based on the results of this study concluded that learning under volleyball passing through modification bolvi compass games can improve learning outcomes volleyball in grade V Elementary School District 01 Duwet Bojong Kab Pekalongan.